Penggunaan Model Pembelajaran Wordwall dalam Meningkatkan Minat Belajar Matematika Materi Bangun Ruang Pada Siswa Kelas 2 MI Nurul Huda Kota Bengkulu - Annisa Nur Hasanah; Fadilah Fadilah; Siti Kholifah; Windamayanti Pohan (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Math is still considered difficult, and tends to be less interesting for students, so it requires the development of the use of interactive learning models such as wordwall. The purpose of this study is to map and analyze the use of the wordwall learning model in increasing interest in learning mathematics in space building materials in 2nd grade students of MI Nurul Huda, Bengkulu City. Using the classroom action research method (PTK) approach involving 25 students, it was carried out in two cycles, each cycle consisted of planning, implementation/action, observation, and reflection. The results of the study show that the use of the wordwall learning model can increase interest in learning mathematics in building materials, this can be seen in pre-cycle activities the interest in learning mathematics in students' building materials is only 62.4%, in the first cycle it increases to 72%, and in the second cycle it increases to 80%. The increase in interest in learning mathematics in this space-building material shows that the wordwall learning model is able to change the learning atmosphere more fun and interactive, so that there is an increase in interest in learning mathematics in students. Therefore, it can be suggested that, to increase interest in learning mathematics in building materials, increase the use of the wordwall learning model in madrasah.Keywords: Usage, Wordwall Learning Model, Interest in Learning Mathematics Spatial Building Materials, Madrasah Ibtidaiyah (MI) Nurul Huda Bengkulu City. Abstrak: Matematika masih dianggap sulit, dan cenderung kurang menarik bagi siswa, sehingga membutuhkan pengembangan penggunaan model pembelajaran yang interaktif seperti wordwall. Tujuan penelitian ini untuk memetakan dan menganalisis penggunaan model pembelajaran wordwall dalam meningkatkan minat belajar matematika materi bangun ruang pada siswa kelas 2 MI Nurul Huda Kota Bengkulu. Menggunakan pendekatan metode penelitian tindakan kelas (PTK) dengan melibatkan 25 siswa, dilaksanakan dalam dua siklus, setiap siklusnya terdiri dari perencanaan, pelaksanaan/tindakan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran wordwall dapat meningkatkan minat belajar matematika materi bangun ruang, hal ini terlihat pada kegiatan pra siklus minat belajar matematika materi bangun ruang siswa hanya sebesar 62,4%, pada siklus I meningkat menjadi 72%, dan pada siklus II meningkat menjadi 80%. Peningkatan minat belajar matematika materi bangun ruang ini menunjukkan bahwa model pembelajaran wordwall mampu mengubah suasana belajar lebih menyenangkan dan interaktif, sehingga terjadi peningkatan minat belajar matematika pada siswa. Oleh karena itu dapat disarankan bahwa, untuk meningkatkan minat belajar matematika materi bangun ruang, maka tingkatkanlah penggunaan model pembelajaran wordwall di madrasah.Kata kunci: Penggunaan, Model Pembelajaran Wordwall, Minat Belajar Matematika Materi Bangun Ruang, Madrasah Ibtidaiyah (MI) Nurul Huda Kota Bengkulu.